Cambodia : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2006)
The Joint Staff Advisory Note (JSAN) reviews the National Strategic Development Plan (NSDP)-the new Poverty Reduction Strategy Program of Cambodia. It recommends that the institutional arrangements for NSDP should be strengthened to support its implementation and monitoring. It analyzes that there is a need for financial assistance, the integration of planning and public financial management, and links for monitoring annual progress targets. The JSAN appreciated the strong macroeconomic performance under the NSDP and emphasized for the need for good governance, strong strategy implementation, and consolidation of existing programs and policies.